Gain variation of 60‐GHz patch antennas due to ground plane dimensions. Issue 4 (April 2016) - Seo, Haekyo; Hong, Wonbin; Gun Kam, Dong
ABSTRACT: Designing phased‐array antennas for millimeter‐wave systems becomes difficult because of anomalous gain variation across elements. The performance of each antenna element varies significantly depending on its location on a finite ground plane. Based on simulation and measurement of 60‐GHz patch antennas, we explain which design parameters determine specific gain variations. © 2016 Wiley Periodicals, Inc. Microwave Opt Technol Lett 58:745–747, 2016